ANALYSIS OF RISK FACTORS FOR STUNTING AMONG CHILDREN UNDER FIVE YEARS OLD IN INDONESIA'S COASTAL AREAS: LITERATURE REVIEW - Sukarya, Shola Shobrina; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The initially five years of life are a critical period, during which development and growth become determinants of a child's success in subsequent stages of development. The World Health Organization describes stunting as a growth and development disorder in children resulting from chronic malnutrition and repeated infections, characterized by below-standard height or stature. In 2020, the World Health Organization reported that 22 percent or 149.2 million children experienced stunting. The Ministry of Health's Nutritional Status Survey stated that the Happening of stunting in Indonesia had decreased to 21.6 percent in 2022. East Nusa Tenggara has the highest Happening of stunted toddlers at 35.3 percent, while Bali has the lowest Happening at 8 percent in Indonesia. The has the purpose of this research is to determine the risk determinants for stunting in toddlers, especially in coastal areas of Indonesia. Literature review was determined by searching articles in the Google Scholar and PubMed databases systematically utilizing keywords "Stunting," "Toddlers," and "Coastal" in both Indonesian and English languages. Articles were selected based on predetermined inclusion and exclusion criteria. Based on the review, the risk determinants for stunting in coastal areas include the child's gender, mother's education and income, energy intake, mother's caregiving patterns, feeding patterns, exclusive breastfeeding, record of transmissible disorders, birth weight and length, mother's height, mother's BMI, and environmental Cleanliness. Among these determinants, the most influential, based on various reviewed journals, are maternal education, environmental Cleanliness, energy intake, and feeding patterns. Keywords: Children, Coastal Area, Stunting